Antifungal Selection for the Treatment of Onychomycosis: Patient Considerations and Outcomes - Axler E; Lipner SR (Infection and Drug Resistance, 2024)
Eden Axler, Shari R Lipner Weill Cornell Medicine, Department of Dermatology, New York, NY, 10021, USACorrespondence: Shari R Lipner, Weill Cornell Medicine, Department of Dermatology, 1305 York Avenue, New York, NY, 10021, USA, Tel +1 646-962-3376, Fax +1 646-962-0033, Email shl9032@med.cornell.eduAbstract: Onychomycosis, a common fungal nail infection, affects > 20% of adults over age 60 and > 50% of people over age 70. Onychomycosis may cause pain, psychosocial problems, and secondary infections, therefore meriting treatment. This review describes the range of treatment modalities, including FDA-approved systemic drugs and topical therapies. Additionally, new and emerging oral and topical therapies are discussed. We emphasize the importance of tailoring onychomycosis therapy to individual patient characteristics, comorbidities, preferences, extent of nail involvement, and fungal species, such that physicians may optimize treatment outcomes, patient satisfaction, and safety.Keywords: dermatophyte, nail infection, topical therapy, systemic treatment, fungal susceptibility, treatment guidelines